Penerapan Sanksi Pidana Terhadap Nakhoda dan Anak Buah Kapal Yang Melakukan Tindak Pidana Penambangan Tanpa Izin di Wilayah Hukum Direktorat Perairan dan Udara Polda Jambi - Rahman, Abdul; Muslih, M; Alamsyah, Bunyamin (Legalitas: Jurnal Hukum, 2025)
The crime of unlicensed mining by means of a ship was discovered during a raid by the Directorate of Water and Air Police of the Jambi Regional Police. Furthermore, the ship, captain and crew were secured by Ditpolairud Polda Jambi for examination. could not show a mining permit and was not in accordance with the shipping operational permit. The application of punishment against the captain and crew of the ship, must be followed by the concept of criminal responsibility starting with the behavior / actions committed that meet the elements of guilt. The purpose of this study is to understand and analyze the application of criminal sanctions against shipmasters and crew members who commit criminal acts of mining without a permit in the jurisdiction of the Jambi Police Air and Water Directorate and the application of sanctions as a form of responsibility for shipmasters and crew members who commit criminal acts of mining without a permit in the jurisdiction of the Jambi Police Air and Water Directorate has provided justice. This research uses an empirical juridical approach. The application of criminal sanctions against Ship Captains and crew members who commit criminal acts of unlicensed mining in the jurisdiction of the Jambi Police Waters and Air Directorate has been investigated and investigated by Investigators based on errors that have been violated based on applicable regulations, especially Law Number 3 of 2020 concerning Minerals and Coal by first conducting a case title and following the stages in the criminal justice system process. The application of sanctions as a form of accountability for the Skipper and Ship's crew who committed the crime of unlicensed mining in the jurisdiction of the Jambi Police Waters and Air Directorate has not fulfilled justice for the perpetrators because the imposition of imprisonment given equally to all defendants without giving consideration to aggravating criminal sanctions because the duties and responsibilities of the defendant as a skipper are leaders in ship operations who give orders to the crew.